(3GdeSJbfY TQM eNJUQ GdebfYs - (3efUhQ Hf jhfS Hf UdGM GdOjf GHf MSf Hf EOQjS GdHghJj GdMfHdj , J (B1051 (3g` s; (3ehSi Hf CMeO Hf ehSi Hf SGde Hf YjSi Hf SGde GdnMnqLGhj GdebOSj, Ke GdUGdMj, TQa GdOjf, CHhGdfLG,J (B968 (3g` s
(3ChdgG (B:s
(3Udi Gddg Ydjg hSde hSei eKjd GdCYVGA Ydi hLg GdeNUhU s
(3BNQgG (B:s
(3hdh GbQ HHSJGf jTed GdCTLGQ hTLQg JTed GdCZUGf hgPG BNQ eG JjSQ LeYg s
(3GdeSJfbY dCHi GdfLG gh GNJUGQ ddcJGH (B" (3GdebfY (B" (3dGHf bOGeg GdebOSi GfXQ cTa GdXfhf Le (B2 (3U` (B1809s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B320 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B34s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs